2010
DOI: 10.1148/radiol.10091937
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease: Longitudinal Hyperpolarized3He MR Imaging

Abstract: For this small pilot group of ex-smokers with COPD, (3)He MR imaging-derived VDV, VDP, and ADC measurements worsened significantly, but there was no significant change in FEV(1), suggesting increased sensitivity of hyperpolarized (3)He MR imaging for depicting COPD changes during short time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 46 publications
4
81
1
Order By: Relevance
“…Woodhouse et al (29) showed no relationship between hyperpolarized 3 He MR ventilation imaging and spirometry. Other investigators have reported a significant correlation between spirometry and hyperpolarized 129 Xe and 3 He MR imaging-derived ventilation defect percentage (27,30). Similarly, contrasting significant correlations (31) and weak associations (30) between hyperpolarized 3 He MR imaging-derived ADC and spirometric measurements are published in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Woodhouse et al (29) showed no relationship between hyperpolarized 3 He MR ventilation imaging and spirometry. Other investigators have reported a significant correlation between spirometry and hyperpolarized 129 Xe and 3 He MR imaging-derived ventilation defect percentage (27,30). Similarly, contrasting significant correlations (31) and weak associations (30) between hyperpolarized 3 He MR imaging-derived ADC and spirometric measurements are published in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, the fi eld transitioned to using helium 3 ( 3 He), which offered a simpler and more mature polarization technology ( 3 ), a large magnetic moment, and absence of physiologic effect. Hyperpolarized 3 He MR imaging entered clinical research in 1996 ( 4,5 ), expanded to multicenter studies ( 6 ), has shown signifi cant correlation to conventional techniques (eg, spirometry, diffusing capacity, radiography) ( 7-10 ), and has enabled longitudinal studies by virtue of its noninvasive nature ( 11 ). Recent years have seen the addition of numerous contrast mechanisms, including the apparent diffusion coeffi cient as a sensitive marker of emphysema ( 7,12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a recent single photon emission computed tomography/CT and multiple breath nitrogen washout study ( 17 ) reported no significant change in ventilation heterogeneity after tiotropium administration. Pulmonary magnetic resonance (MR) imaging with hyperpolarized helium 3 ( 3 He) has emerged as a functional imaging method that provides high-spatialresolution and high-temporal-resolution (18)(19)(20)(21)(22)(23) images of the lung. Regional ventilation abnormalities are clearly visualized as areas of decreased 3 He signal in the lung that can be scored or quantifi ed with the metric ventilation defect percentage (VDP) ( 19 ) or percentage ventilated volume ( 24 ).…”
Section: Patientsmentioning
confidence: 99%